ศักดิ์ศรีความเป็นมนุษย์ของคนไร้สัญชาติและคนไร้รัฐภายใต้รัฐธรรมนูญแห่งราชอาณาจักรไทย พุทธศักราช 2550 - วีรวัฒน์ อิสรานุวรรธน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
The term "Human Dignity" was guaranteed in Article 4 of the Constitution of the Kingdom of Thailand B.E. 2550. After the entry into force of such provision, there were some interpretation problems, whether the constitutional guarantee of human dignity covers only Thai citizens or including the nationalityless persons and stateless persons. If the said provision did not provide an adequate level of protection to the nationalityless persons and stateless persons, these persons will have no "human dignity" rights against the infringement. On the other hand, if the said constitutional provision covers the nationalityless persons and stateless persons, it must be kept under close review, whether Thailand has undertook to ensure the content and rationale of human dignity for the nationalityless persons and stateless persons. The study found out that the human dignity of nationalityless persons and stateless persons is still wrongfully violated oppressed and exploited in various kinds of forms. They also do not have fundamental to live normally in adequate level as one human being needs to have, the reason for this is that the problems of public policy and racial prejudice against the nationalityless persons and stateless persons, especially from government officials. And last but not least, there is no international resolution to cope with the problems of nationalityless persons and stateless persons. This thesis has aimed to study the problems of the violation of human dignity of the nationalityless persons and stateless persons, while the Constitution of the Kingdom of Thailand, B.E.2550 has guaranteed such human dignity. Moreover, Thailand is bound itself under the international treaties that encourage equality of human beings. This study will determine the cause of the violation of the human dignity of the nationalityless persons and stateless persons to find proper conclusions that can be used to solve and protect the human dignity under the Constitution. And the human dignity of the nationalityless persons and stateless persons will become tangible right. Finally the problems of the violation of human dignity of the nationalityless persons and stateless persons will be entirely eradicated.